Meningkatkan Kemampuan Berhitung Pengurangan Siswa Kelas 1 SD Dengan Metode Bermain Puzzle Matematika di SDN 104202 Bandar Setia - Putri Wirdani; Nur Wahyuni (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to improve the mathematical subtraction calculation ability of class I-A students of SDN 104202 Bandar Setia through the puzzle playing method. The problem in this study is low mathematics learning outcomes. The method used in the study is Classroom Action Research (CAR) as many as 2 cycles. The subjects of this study were class 1-A students at elementary school SDN 104202 Bandar Setia Jl. Terusan Dusun V Bandar Khalipah, Percut Sei Tuan District, Deli Serdang Regency, 2024/2025 Academic Year, totaling 27 students consisting of 10 female students and 17 male students. Classroom Action Research (CAR) improves students' subtraction calculation ability by using the mathematical puzzle playing method of class 1 SDN 104202 Bandar Setia, it can be concluded as follows: "The application of the mathematical puzzle playing method in class 1-A SDN 104202 Bandar Setia which is proven by an increase in research results in each cycle. Assessment of achievement in mathematics learning subtraction in cycle I with an average of 69.25, percentage of completion 69%, and in cycle II began to show an increase with an average value of 90.74 percentage of completion 90%. The results also show that this classroom action research achieved the specified completion indicator, namely completion above 90% .